Incorporation of detailed eye model into polygon-mesh versions of ICRP-110 reference phantoms. (28th October 2015) - Nguyen, Thang Tat; Yeom, Yeon Soo; Kim, Han Sung; Wang, Zhao Jun; Han, Min Cheol; Kim, Chan Hyeong; Lee, Jai Ki; Zankl, Maria; Petoussi-Henss, Nina; Bolch, Wesley E; Lee, Choonsik; Chung, Beom Sun
Abstract: The dose coefficients for the eye lens reported in ICRP 2010 Publication 116 were calculated using both a stylized model and the ICRP-110 reference phantoms, according to the type of radiation, energy, and irradiation geometry. To maintain consistency of lens dose assessment, in the present study we incorporated the ICRP-116 detailed eye model into the converted polygon-mesh (PM) version of the ICRP-110 reference phantoms. After the incorporation, the dose coefficients for the eye lens were calculated and compared with those of the ICRP-116 data. The results showed generally a good agreement between the newly calculated lens dose coefficients and the values of ICRP 2010 Publication 116. Significant differences were found for some irradiation cases due mainly to the use of different types of phantoms. Considering that the PM version of the ICRP-110 reference phantoms preserve the original topology of the ICRP-110 reference phantoms, it is believed that the PM version phantoms, along with the detailed eye model, provide more reliable and consistent dose coefficients for the eye lens.